LIMITATIONS OF TRADITIONAL METHODS IN TRAINING SIMULTANEOUS INTERPRETERS (International journal of artificial intelligence, 2026)
The aim of this article is to identify the limitations of traditional methods in training simultaneous interpreters and evaluate their effectiveness in the context of modern educational demands. The study focuses on key issues such as the overemphasis on theoretical instruction, insufficient practical training, and the limited integration of modern technologies into the learning process. The problem statement highlights that traditional teaching approaches do not fully meet current market requirements and fail to adequately develop real-time decision-making skills in trainee interpreters.The methodology of the study includes analytical review, comparative analysis, and pedagogical observation. In further stages, statistical data will be incorporated to ensure a more precise and evidence-based evaluation of the findings. The main findings indicate that traditional methods often neglect cognitive load factors and are insufficient in developing rapid processing and response skills required for simultaneous interpretation. The discussion emphasizes the need to adopt innovative, technology-enhanced, and interactive teaching approaches.In conclusion, the study suggests that traditional methods should be reconsidered and supplemented with modern pedagogical strategies to improve the overall quality of interpreter training.